New development: 'Healing at a distance'-telemedicine and COVID-19 - Leite, Higor; Hodgkinson, Ian R.; Gruber, Thorsten (Public money & management, 2020)
In extreme circumstances such as pandemics, the presence of patients in hospital emergency departments becomes untenable. Healthcare professionals and organizations worldwide are leaning on technology as a crucial ally to deal with the COVID-19 outbreak. This article focuses on the positive impact of telemedicine for helping service provision, from enabling virtual triage to mitigating the negative psychological effects of social isolation. The authors discuss the challenges and opportunities to telemedicine practices. This article explains how telemedicine and other e-healthcare technologies can benefit people, medical staff and healthcare systems. One of the main challenges for telemedicine in many countries is the lack of regulations. The authors call on policy-makers to facilitate wider implementation of e-healthcare technologies, while considering issues of inclusiveness, privacy and data protection. The article informs managers about the use of new technologies. Examples are provided of e-healthcare technologies implemented during the COVID-19 pandemic, for example in terms of healthcare capacity and providing support to people affected by quarantine.